THE CONCEPT OF CITIZENSHIP FROM THE PERSPECTIVE OF MARTA ARRETCHE: BRIEF ANALYSIS OF THE IMPLICATIONS FOR PUBLIC POLICIES AND INEQUALITY (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The present research aims to discuss the concept of citizenship from the perspective of Marta Arretche, highlighting the importance of analyzing the concept of citizenship for the elaboration, application and access of citizens to public policies in favor of combating social inequality in Brazil. For Arretche (2018), the definition of citizenship has more than one dimension, going beyond the granting of civil and political rights. In view of this, citizenship encompasses the active capacity of individuals to participate in decisions that impact their lives, as well as the right to a minimum of well-being and security, consolidated in equitable access to services and opportunities. Studies support the essentiality of constant reforms in public policies to ensure that all citizens can enjoy their rights. The methodology of this article is qualitative and analytical, based on the analysis of Marta Arretche's academic production on citizenship and public policies. Although the research focuses on Marta Arretche's perception, other literary and academic productions will also be used with the aim of collaborating with the development of this study.Keywords: Citizenship, Marta Arretche, Public Policies; inequality